Syrah Grape Polyphenol Extracts Protect Human Skeletal Muscle Cells from Oxidative and Metabolic Stress Induced by Excess of Palmitic Acid: Effect of Skin/Seed Ripening Stage - Adriana Capozzi; Auriane Dudoit; Luca Garcia; Gilles Carnac; Gérald Hugon; Cédric Saucier; Catherine Bisbal; Karen Lambert (Antioxidants, 2024)
Metabolic skeletal muscle (SM) dysfunction, triggered by increased oxidative stress and mitochondrial impairment, is a pivotal contributor to obesity-associated insulin resistance (IR). Addressing obesity and SM IR demands substantial lifestyle changes including regular exercise and dietary adjustments that are difficult to follow over time. This prompted exploration of alternative approaches. Grape polyphenols (GPPs) have demonstrated a positive impact on metabolism, although few studies have focused on SM. Since grape polyphenolic content and composition depend on tissue and ripening, we explored the antioxidant potential of GPPs from skin (Sk) and seeds (Sd) extracted before veraison (Bv) and at mature (M) stages, on palmitate-induced IR in primary human SM cells. Despite their important difference in polyphenol (PP) content: Sd-BvPP > Sd-MPP/Sk-BvPP > Sk-MPP, all extracts reduced lipid peroxidation by 44–60%, up-regulated the heme-oxygenase 1 protein level by 75–132% and mitochondrial activity by 47–68%. Contrary to the other extracts, which improved insulin response by 50%, Sd-BvPP did not. Our findings suggest that compounds other than stilbenoids or anthocyanin-type molecules, present only in grape Sk, could play an active role in regulating SM oxidative and metabolic stress and insulin sensitivity, paving the way for further exploration of novel bioactive compounds.